Arbitration as a Method of Dispute Resolution in Islamic Banking in Malaysia - Abdul Majid Tahir, Mohamed; Noor ‘Ashikin, Hamid; Maheran, Makhtar; Khairun-Nisaa, Asari (2015)
Arbitration is one of important alternative dispute resolution (ADR) methods. Being an alternative method, it had advantages over the conventional dispute resolution method i.e court litigation. This paper is to examine the application of arbitration as a method of resolving disputes in islamic banking in Malaysia. This paper adopts library research method whereby analysis is done to relevant statutory laws, decided cases, books, journals, law reports, newspapers articles, conference proceedings and other periodicals. This paper concludes that although the law and bodies related to arbitration in islamic banking in Malaysia are already in place, few improvements could be done to ensure the arbitral process is more in line with Shariah.